Impacts of Ethnic-consciousness on Political Development of Nigeria’s Fourth Republic - Obaka, James Ocheni (Social Science Research, 2022)
Nigerians have never benefited from the much desired development after independence since 1960 in spite the uninterrupted democracy for over two decades. This is due to the discrimination among the citizens in their political participation. The political elite are highly divided along ethnic and religious linesfor their selfish gains since the First Republic. This is due to the amalgamation of the Northern and Southern protectorates in 1914 by the British colonialist. Nigeria had hardly ever been united as a nation. People from each region treat others as aliens resulting in lack of trust, hatred and fear of each other.Politicians use the situation and base their campaigns on religion and tribal affiliations instead of ideology. It resulted in the military coups d’etats of 1966 and 1983 respectively. In spite of the rich human and natural resources of Nigeria, majority of Nigerians remain poor. The objectibe of thepaper is to interrogate the effects of ethnic consciousness on the political development of Nigerian Fourth Republic and recommend the solution to the menace. The paper uses qualitative method of research with data gotten from secondary sources. It adopts integration theory which among others presupposes that citizens of a country need to be united for peace and development to thrive. Fourth Republic post-democratic elites have the responsibility of uniting Nigerians for the provision of the much desired good governance. To this end, the paper recommends that the Fourth Republic politicians adhere to politics of ideology and get rid of ethno-religious politics of divide and rule.